Risk management in sport and recreation - Spengler, John O. 1962- (John Otto); Pittman, Andrew T. 1945- (Human Kinetics, 2006)
Risk Management in Sport and Recreation is a comprehensive resource for those charged with the responsibility of providing for the safety of participants and spectators in a sport or recreation setting. It covers a range of safety issues, including lightning, heat illness, aquatics, playground safety, drug testing, and medical emergency action plans. Readers receive clear and detailed explanations of issues to consider before making decisions on risk management. Risk Management in Sport and Recreation is designed to provide a foundation for approaching key issues in safety and risk management. It shows readers how to evaluate and analyze various safety issues and apply the underlying concepts to a variety of situations. The following are unique features of the text: A safety guidelines finder lists Web sites of accessible standards, guidelines, and recommendations from leading organizations; Chapter objectives and pullout boxes of key points and key statistics stress the importance of the topic under discussion; Threshold issues in each chapter highlight important factors to consider when making decisions on risk management; Real-world applications at the end of each chapter present scenarios involving the potential for harm, and readers must make a decision on how to address the issues; Examples of public service announcements, posters, and other publicly viewed safety information are presented; An appendix offers examples of emergency action plans, checklists, and recommendations from organizations such as the National Lightning Safety Institute and university aquatic centers. The safety guidelines finder gives students and practitioners a single location from which they can easily access important safety information. Organized under land-based or water-based activities, each activity lists guidelines, recommendations, and standards along with the source for that information. Each entry includes Web sites where readers can find the full documents. The text also features sample guidelines and safety checklists from agencies and associations that demonstrate how organizations might plan for risk and communicate safety information. Readers also consider the types of postings and equipment they will need in order to communicate their risk management plans, and they are given real-life situations in which a risk management plan is needed and are prompted to consider why and how to create a plan for such situations. The resource will help students and professionals plan for and manage risk. Current and future employees of sport facilities, school athletic programs, parks and recreation programs, youth and aquatic centers, or resorts and golf courses will find that Risk Management in Sport and Recreation provides the tools to assist in making the right decisions to manage risk effectively.